Media Sosial dan Gerakan Sosio-Politik Umat Islam di Indonesia - Taufiq, Firmanda; Utama, Lalu Wahyu Putra (FIKRAH, 2018)
Today's technological developments have a broad impact on people's lives, including religious areas. The ease of access to information does not have a positive impact on Islamic da'wah but is also used as a provocative tool, as it ensnares Ahok. The purpose of this article is to examine how social media is used to spread the news about the condition of Muslims in Indonesia. The method used in this article is descriptive analysis by reviewing and examining the information content of social media, especially the news of the Islamic community in Indonesia. The implications of this article are expected to provide a clear picture of how social media is used in the social and political movements of Muslims in Indonesia. The result is that the media has a strategic position in describing, conceptualizing and influencing a community phenomenon.